Faktor – Faktor Yang Berpengaruh Terhadap Kompetensi Literasi Digital Mahasiswa di Era Revolusi Industri 4.0 - Dhian Rosalina; Kartika Yuliari; Dias Setianingsih; Muhammad Rizqi Zati (Fakultas Ekonomi Universitas Kadiri, 2021)
This study aims to identify the factors that influence the digital literacy competence of students in the era of the industrial revolution 4.0. This research was conducted at the Faculty of Economics, Kadiri University the sampling technique used was purposive sampling, with one hundred students as respondents. The analysis used Confirmatory Factor Analysis, the results of the study show that there are three factors that affect the level of digital literacy competence of students, including: 1) environmental support factors consisting of campus environment and family roles, 2) socio-economic conditions which include individual financial conditions critical of the media, and 3) the intensity of media use which consists of the use of digital media in daily activities and work on academic assignments.